Role of Cooperatives in Women Empowerment in the Nepalese Context - Khatri Basnet, Rati (Cognition, 2023)
Cooperatives are important income-generating organizations. They help rural women in many ways. This study aims to identify the contribution of cooperatives to economic, socio-cultural, and political aspects of women empowerment. When women are empowered, they can uplift the economic condition of their families. The objectives of the study is to find out the role of cooperatives in women empowerment. The study is based on descriptive and analytical method. The secondary data are collected from different national and international research articles. This study has found that there is a significant difference in the economic, socio-cultural, and political empowerment of women. Women members are found empowered in their economic activities, maintain social relationships, reduce gender disparity, involve in social programs, conduct cultural programs and participate in political programs. The cooperatives can uplift the socio-economic condition of rural and urban women through access to financial services. They can provide other development services and alleviate poverty through women's empowerment. They have expanded their network of relationships through saving and credit programs. The study shows the need for expansion programs in hard-to-reach areas to empower economically, socially, culturally, and politically disadvantaged groups.